Integration of Governance, Risk, and Compliance and Environmental, Social, and Governance for the Indonesian Banking Sector - Jerry Marmen Simanjuntak; Airlangga Surya Kusuma; Kevin Naufal Widyadhana (Borong Newinera Publisher, 2026)
Coordination of state intelligence is one source of problems which also This article explores the integration of Governance, Risk, and Compliance (GRC) with Environmental, Social, and Governance (ESG) in the banking sector. The integration of GRC and ESG, known as ESGRC, plays a crucial role in mitigating both financial and non-financial risks, enhancing reputation, and creating long-term value through smarter risk management and sustainable governance. Additionally, ESGRC facilitates better responses to global challenges such as climate change and social inequality while unlocking new opportunities in sustainable finance, including carbon trading and green financing. Other strategic benefits include improved transparency, accountability, and corporate performance. However, the article highlights several major challenges, including the need for investment in advanced technologies like Big Data and Artificial Intelligence, as well as the cultural shifts required to support ESGRC adoption. Regulations like POJK 51/2017 and POJK 14/2023 in Indonesia serve as key drivers for ESGRC implementation, though global uncertainties remain significant barriers.